PENCEGAHAN PENYIMPANGAN PERILAKU SOSIAL MELALUI BIMBINGAN IMTAQ - Nuruddin; Muhamad Ahyar Rasidi (Indonesian Society and Religion Research, 2024)
This research is qualitative research that aims to obtain an overview of strategies for preventing student social behavior deviations. Imtaq activities are a forum for cultivating students' morals. Through moral education, it is hoped that it can guide humans on a better path and of course, good and useful moral education will have a lot of influence on every side of human life itself. Teachers have a strategic role in the teaching and learning process. Teachers prepare students to become productive citizens, think critically about society and their lives, build character, and have a social spirit. Efforts to prevent social behavior are carried out with various programs, including increasing teacher and student discipline, routinizing the Imtaq program every morning, and increasing teacher spirituality. The obstacle faced is that several program innovations have not run well